Growth of agro-industrial complex in modern economic conditions - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Духневич, Андрій Вікторович; Духневич, А. В.; Духневич, Андрей Викторович; Dukhnevych, Andrii V.; Клюца, Сергій Олександрович; Клюца, С. О.; Клюца, Сергей Александрович; et al. (Universidad San Gregorio de Portoviejo, 2020)
The long-term, stable development of the country, the standard of living of its population is primarily influenced by the ability of the state to fully meet the basic needs of the population, a prominent place among which is the nutritional requirement. At the same time, the level of meeting the population’s nutritional requirements is put into practice through the assessment of such a category as food security. Its sustainability to a great extent depends on the success of the development and functioning of the agro-industrial complex of the country, which is constantly affected by climatic factors, economic and financial, as well as political ones. The introduction of quarantine worldwide in connection with the spread of coronavirus infection is a striking example of this impact, which ultimately has shown the need to ensure high food security and made this study relevant. In consideration of the foregoing, in this research we have revealed the level of food supply in the world, as well as studied the countries with the highest and lowest levels of food sustainability. Along with this, the scientific study has determined the volume of the gross value added of the agricultural industry in the context of basic prices, as well as the level of investment in agriculture in European countries, which made it possible to draw conclusions concerning the level of development of the agricultural sector in the represented countries and to monitor the interconnections with changes in food security level and gross value added in the industry over the outlined period. The level of exports and imports in Europe for 2010-2019 has been determined by forming a forecast of changes in the balance between these indicators for 2020-2022. Methods of analysis, synthesis, formalization, logical abstraction, theoretical cognition, monographic, systematization, abstract-logical and others have been used to carry out the investigation. As a result of the analysis performed in the academic paper it has been established that it is necessary to stimulate the development of the agro-industrial complex in Asia, Africa, Latin America and the Caribbean. One of the tools for such stimulation is the implementation of the strategy for the development of the agro-industrial complex for the long-term perspective, along with the use of tactical programs and measures to achieve common development goals. At the same time, the study has determined that the development and implementation of the strategy should be carried out in symbiosis with international, regional, state and municipal strategies; it is a key factor for their success.

На довгостроковий стабільний розвиток країни, рівень життя її населення насамперед впливає здатність держави повністю задовольняти основні потреби населення, чільне місце серед яких займає потреба в харчуванні. При цьому рівень задоволення потреб населення в харчуванні реалізується на практиці через оцінку такої категорії, як продовольча безпека. Від її стійкості значною мірою залежить успішність розвитку та функціонування агропромислового комплексу країни, на який постійно впливають кліматичні фактори, економічні та фінансові, а також політичні. Яскравим прикладом такого впливу є запровадження карантину в усьому світі у зв’язку з поширенням коронавірусної інфекції, який в кінцевому підсумку показав необхідність забезпечення високої продовольчої безпеки та зробив дане дослідження актуальним. Враховуючи вищевикладене, в даному дослідженні ми виявили рівень забезпечення продовольством у світі, а також вивчили країни з найвищим і найнижчим рівнями продовольчої стійкості. Поряд з цим, наукове дослідження визначило обсяги валової доданої вартості сільськогосподарської галузі в розрізі базових цін, а також рівень інвестицій у сільське господарство європейських країн, що дозволило зробити висновки щодо рівня розвитку аграрного сектору в представлених країнах та відслідковувати взаємозв'язки зі змінами рівня продовольчої безпеки та валової доданої вартості в галузі за окреслений період. Рівень експорту та імпорту в Європі на 2010-2019 роки визначено шляхом формування прогнозу зміни балансу між цими показниками на 2020-2022 роки. Для проведення дослідження використано методи аналізу, синтезу, формалізації, логічної абстракції, теоретичного пізнання, монографії, систематизації, абстрактно-логічні та інші. У результаті проведеного в науковій роботі аналізу встановлено, що необхідно стимулювати розвиток агропромислового комплексу в Азії, Африці, Латинській Америці та Карибському басейні. Одним із інструментів такого стимулювання є реалізація стратегії розвитку агропромислового комплексу на довгострокову перспективу, а також використання тактичних програм і заходів для досягнення спільних цілей розвитку. Водночас дослідження визначило, що розробка та реалізація стратегії повинна здійснюватися в симбіозі з міжнародними, регіональними, державними та муніципальними стратегіями; це ключовий фактор їхнього успіху.
Petrunenko I. Growth of agro-industrial complex in modern economic conditions / I. Petrunenko, A. Dukhnevych, S. Kliutsa, N. Karpinska, O. Demianyshyna // Revista San Gregorio. - № 42. - Universidad San Gregorio de Portoviejo, 2020. - P. 131-143.
Keywords: food security; agro-industrial complex; food sustainability; level of malnutrition; gross value added of the industry; agro-industrial development strategy; selfsufficiency; gross fixed capital formation in agriculture; продовольча безпека; агропромисловий комплекс; продовольча стійкість; рівень недоїдання; валова додана вартість галузі; стратегія агропромислового розвитку; самозабезпеченість; валове нагромадження основного капіталу в сільському господарстві; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Economics